Study on Manufacturing Based on Feature Recognition Using NX - Stanasel, I.; Blaga, F. S.; Buidos, T. (New Approaches in Engineering Research Vol. 15, 2021)
Competition in the market causes companies to update continuously their products both in terms of design and performance and in terms of manufacturing technologies to ensure high performance, low cost and manufacturing time. The integration of Computer Aided Design (CAD) applications with Computer Aided Manufacturing (CAM) applications has led different researchers to study the concept of recognition of features in as many activities as possible that contribute to the achievement of a product, starting from design, manufacturing, production planning, assembly, quality management. In order to make the production process more efficient, it was approached the automatic realization of the programs for numerically controlled (CNC) machine tools based on the characteristics of the features that make up the part. The paper presents a case study on how to perform machining programs on CNC machine tools using the facilities offered by Siemens NX application based on feature recognition.